The Revolution of 1908 in Turkey: Leiden: Brill. pp. 341 +xii. ISBN: 90-04-10791-6 (HB). (American Journal of Islam and Society, 2001)
This is a book version of Kansu's doctoral thesis, in which his objective"was to show [the political] transformation [in the beginning of thecentury]-however elusive- by re-telling the political history of modemTurkey in a radically different fashion" (p. ix). He states that this radicalapproach is based on an '"historical' viewpoint [which is) opposed to a'political' one"(p. ix).In order to show his radical re-telling of the political transformation of theOttoman Empire in the beginning of the previous century, the bookcommences with a critical but analytical and enjoyable chapter on Turkishhistoriography by making special emphasis on the interpretation of theRevolution of 1908. In doing so, Kansu summarises the attitudes of theTurkish academics and intellectuals towards the interpretation of recentTurkish history. This in tum is an attempt to clarify his ideological standas regards the Kemalist revolution of 1923 and the Young Turks.The first concept the reader encounters with the first chapter is'Revolution'. For Kansu the year 1908 is the most crucial year in modemTurkish history, "because a new era opens before the Turkish socialformation through a genuine revolutionary movement. 1908 is thebeginning of the establishment -for the first time in modem Turkishhistory- a constitutional monarchical form of government whichlegitimates itself on the presence of a representative parliament to which itis totally responsible" (p. l). It has to be stated that while the "genuinerevolutionary character" of the constitutional movement is open to question,Ottomans had the first parliamentary political structure not in 1908 butin 1876, albeit it lived only a short while due to Abdulhamid H's politicalambitions and, one has to accept, it was not as strong as the 1908experience in its representation. However, Kansu claims that it was the ...